2006
DOI: 10.1007/s00412-006-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and chromosomal distribution of six Drosophila buzzatii transposons: BuT1, BuT2, BuT3, BuT4, BuT5, and BuT6

Abstract: The abundance and chromosomal distribution of six class-II transposable elements (TEs) of Drosophila buzzatii have been analyzed by Southern blotting and in situ hybridization. These six transposons had been previously found at the breakpoints of inversions 2j and 2q ( 7 ) of D. buzzatii. These two polymorphic inversions were generated by an ectopic recombination event between two copies of Galileo, a Foldback element. The four breakpoints became hotspots for TE insertions after the generation of the inversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Only a few euchromatic signals were observed, although we cannot exclude the possibility that a few dispersed euchromatic copies of PERI remain undetected. Such a pattern of TE accumulation reflects the distribution of genomic regions featuring reduced rates of meiotic recombination and it is most likely to be a consequence of it [Charlesworth et al, 1994;Pimpinelli et al, 1995;Casals et al, 2006]. Interestingly, the distribution of PERI does not seem to overlap with the distribution of the pBuM satDNA in any chromosome, including the X chromosome, where both repetitive DNAs were found in the heterochromatin ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few euchromatic signals were observed, although we cannot exclude the possibility that a few dispersed euchromatic copies of PERI remain undetected. Such a pattern of TE accumulation reflects the distribution of genomic regions featuring reduced rates of meiotic recombination and it is most likely to be a consequence of it [Charlesworth et al, 1994;Pimpinelli et al, 1995;Casals et al, 2006]. Interestingly, the distribution of PERI does not seem to overlap with the distribution of the pBuM satDNA in any chromosome, including the X chromosome, where both repetitive DNAs were found in the heterochromatin ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors noticed that the pattern of hybridization signals generated by cDk27 (probably ␤ -heterochromatin) was different from those detected in the tightly compacted ␣ -heterochromatin, characteristic for satDNAs. In another study, Casals et al [2005Casals et al [ , 2006 showed a preferential accumulation of several class-II transposable elements in pericentromeric zones of polytene chromosomes, defined as transitions between heterochromatin and euchromatin (probably ␤ -heterochromatin). Finally, using PCR, we did not find evidence of interspersion between one of the class II TE elements ( Galileo ) analysed by Casals et al [2005Casals et al [ , 2006, and satDNA repeats [Kuhn et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BuT5 is also quite abundant. In D. buzzatii, BuT5 was found (using in situ hybridization to polytene chromosomes) to be the most abundant of a set of seven transposons, with a basal density of 10 − 2 copies per genome and chromosomal band (Casals et al 2006). BuT5 is particularly abundant as secondary colonizer of the inversion breakpoints, indicating that it is (or has been until very recently) transpositionally active (Delprat et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The three inversions were caused by ectopic recombination between copies of Galileo , a P -superfamily transposon (Marzo et al 2008), and BuT5 was a secondary colonizer of the inversion breakpoints. The secondary colonization of breakpoints in recent polymorphic inversions (Casals et al 2003; Delprat et al 2009) and the relatively high abundance of BuT5 in different D. buzzatii strains (Casals et al 2006) indicate current or recent transpositional activity of BuT5 in D. buzzatii . Furthermore, recent works in our group have revealed that BuT5 generated two recently fixed inversions in two repleta group species, 2s in D. mojavensis (Guillén and Ruiz 2012), and 2x 3 in D. uniseta (Prada 2010).…”
Section: Introductionmentioning
confidence: 99%